Recommendations for the Detection and Mitigation of Laurel Wilt Disease in Avocado and Related Tree Species in the Home Landscape - Jonathan Henry Crane; Jeff Wasielweski; Daniel Carrillo; Romina Gazis; Bruce Schaffer; Fredy Ballen; Edward Evans (EDIS)
Avocado trees are a popular choice for homeowners in Florida, with over 600,000 growing in Florida home landscapes. However, avocado trees as well as others in the Lauraceae family are susceptible to laurel wilt disease, which can kill a tree in as few as three weeks. This new publication of the UF/IFAS Horticultural Sciences Department provides home owners recommendations for identifying and mitigating laurel wilt disease in the home landscape. Written by Jonathan H. Crane, Jeff Wasielewski, Daniel Carrillo, Romina Gazis, Bruce Schaffer, Fredy Ballen, and Edwards Evans. https://edis.ifas.ufl.edu/hs1358